Językowy kształt poradnika gospodarskiego pomieszczonego w „Nowych Wiadomosciach Ekonomicznych i Uczonych" (1758–1761) - Szczaus, Agnieszka (Slavia Occidentalis, 2019)
The article analyses the structural, pragmatic, cognitive and stylistic aspects of a handbook entitled Introduction to governance, featured in the first Polish popular-scientific journal – “Nowe Wiadomości Ekonomiczne i Uczone” published in Warsaw in 1758–1761 by Wawrzyniec Mitzler de Kolof. It has been demonstrated that the text under analysis, which can be classified as a utility text, shows conspicuous elements of two styles – ordinary (unsophisticated vocabulary; simple syntactic structures; proverbs) and scholarly (pronounced text segmentation, perspective of the author setting himself aside from the recipient; economic terminology; defining new or more difficult concepts; references to foreign (Latin and/or German) counterparts of Polish names of plants).